2006
DOI: 10.1001/archinte.166.16.1749
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Child's Chronic Illness on Maternal Sleep and Daytime Functioning

Abstract: Sleep in caregivers of children with chronic illnesses, in particular ventilator dependency, is significantly disrupted, resulting in chronic partial sleep deprivation. Owing to the level of attention and care required by these children, interventions and support for caregivers to improve their sleep quality and quantity are necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
145
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(160 citation statements)
references
References 44 publications
14
145
0
1
Order By: Relevance
“…12,25 Mood disturbances may result from lack of sleep due to nighttime caregiving duties and worries related to the child's health. 26 Sleep deprivation is also associated with limited day-time functioning, decreased cognitive performance and decreased motor function. 27,28 This could contribute to lower vitality and happiness scores in caregivers of children with SCD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12,25 Mood disturbances may result from lack of sleep due to nighttime caregiving duties and worries related to the child's health. 26 Sleep deprivation is also associated with limited day-time functioning, decreased cognitive performance and decreased motor function. 27,28 This could contribute to lower vitality and happiness scores in caregivers of children with SCD.…”
Section: Discussionmentioning
confidence: 99%
“…33 As disrupted sleep patterns have an influence on mood, motor and cognitive functioning, 26 improving sleep quality in caregivers of sickle cell patients is a potentially useful intervention. The effectiveness of behavioral sleep intervention has been demonstrated in caregivers of people with cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The constant care and the difficulties in accomplishing regular daily tasks, and the major dependency of the sick person, might induce a physical overload and, mainly, a psychological overload to the caregivers [21]. This overload might be manifested by means of several symptoms, such as depression [22][23][24] [28], anxiety [24; 29], cardiovascular problems [30], stress [19], and sleep disorders [31][32][33][34].…”
Section: The Caregiver In Duchenne Muscular Dystrophymentioning
confidence: 99%
“…The emotional overload present in the work of a CM indicates the relevance of evaluating the individual perception of sleep quality. Some studies have demonstrated impairment in the caregivers´ subjective sleep quality of children with chronic diseases [31,32]. In caregivers of children with asthma, it was noted a higher number of awakenings and reports of light sleep due to the preoccupation and the vigilance of their sons [39].…”
Section: The Sleep Of Caregiving Mothersmentioning
confidence: 99%
“…In addition to their concern for the child's physical and mental health, mothers are worried about their health and that of their wives, other children and all other family members as well. Many physical (Meltzer and Mindell, 2006;Klassen et al, 2008) (headache, backache, anorexia, digestion disorders, palpitation) and emotional (von Essen et al, 2004;Grinyer, 2006) (senses of weariness, despair, anger, stress, anxiety and depression) problems have been reported by such mothers. Studies even have indicated the existence of the symptoms of the posttraumatic stress syndrome in mothers following treatment (Stuber et al, 1996;Kazak et al, 1997).…”
Section: Introductionmentioning
confidence: 99%